Early vascular aging (EVA) : new directions in cardiovascular protection - Nilsson, P. (Peter); Olsen, Michael H. (Michael Hecht); Laurent, Stephane, 1953- (Elsevier, 2015)
Early Vascular Aging (EVA): New Directions in Cardiovascular Protection brings together the last decade of research related to the characterization of EVA, as well as the predictive power of pulse wave velocity (PWV). The book presents a novel approach to the problem of cardiovascular disease, showing it in relation to great vessels disease and revealing a comprehensive approach to the problem of increased rigidity of the great vessels, its causes, and further consequences. Information provided is accompanied by online access to a supplemental website with video clips of anatomic speci.